Evaluasi Penggunaan Bahan Ajar Pembelajaran Jarak Jauh (PJJ) pada Matakuliah Pengembangan Program Pembelajaran Biologi (P3Bio) - Baiq Muli Harisanti; Titi Laily Hajiriah; I Wayan Karmana (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The spread of the Covid-19 pandemic has forced the government to close schools and encourage the implementation of distance learning. Various ways are used to ensure that learning activities continue, even though there are no face-to-face sessions. To support distance learning, there is a great need for media that is available online and delivered online. The purpose of this study is to describe the impact caused by the use of online teaching materials in distance learning in the Biology Learning Program Development (P3BIO) course which is being implemented in the fourth semester of the 2020/2021 academic year at the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education. The research was carried out by providing research instruments in the form of teaching materials delivered online. The data analysis technique uses the N-Gain formula. The results of data analysis obtained an N-Gain value of 0.48, which when converted into the category of increasing student ability is included in the medium category, indicating an increase between initial knowledge and final knowledge. Thus, the conclusion that can be drawn is that the integration of P3BIO teaching materials is said to be effective, even though they are distributed online through Distance Learning (PJJ).